Experimental study of biosorption of fluoride by immobilized beads of zeolite NaA and Nostoc sp. (BTA394) using a continuous flow system. Issue 6 (20th June 2020) - Mukherjee, Shraboni; Khan, Anoar Ali; Barman, Sanghamitra; Halder, Gopinath
Abstract: The current experiment investigated the fluoride sorptive efficacies of immobilized beads of zeolite NaA and Nostoc sp. (BTA394) from simulated wastewater in column reactor. Influence of crucial kinetic parameters viz. initial concentration (10, 15, and 20 mg/L), bed height (4, 6, and 8 cm) and flow rate (2, 4, and 6 ml/min) on F − uptake was examined. Influence of these parameters on breakthrough curves was also determined. These breakthrough curves were further estimated by Adams–Bohart's and Thomas models. Spent column was eluted with 0.01 M NaCl, Ca(OH)2, Na2 SO4, or NaOH solution to assess column regeneration efficacy. The Thomas model satisfactorily explained the sorption dynamics but Adams–Bohart model could only explicate preliminary portion of the column sorption mechanism. The exhaustion and breakthrough time shortened with increased flow rate, decreased bed height and increased F − concentration. Safe disposal of spent biosorbents were also performed. From the results obtained, it can be said that these biosorbents could be used effectively in treatment of simulated wastewater in continuous flow, although further experiments are being carried out to assess their defluoridation capabilities for real wastewater in large‐scale operations.